2018
DOI: 10.1159/000489753
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic Analysis of Endometrial Tissue from Patients with Ovarian Endometriosis

Abstract: Background/Aims: Ovarian endometriosis (OvE) is ovarian cyst that is lined with endometrial tissue. They are found in 17–44% of women with endometriosis. Their clinical manifestations include pelvic pain, dysmenorrhea, dyspareunia, and infertility. Although the incidence of OvE has increased yearly, the exact pathogenesis of OvE is still unclear. We used peptidomics, an emerging branch of proteomics, to identify differentially expressed peptides in order to determine the possible roles of these peptides in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…For such a complex disease, a biomarker panel that combines several different markers will most likely be more accurate than any single biomarker in the diagnosis of endometriosis. [ 45 ] Studies have confirmed that some biomarker panels such as peptide peaks, [ 57 ] proteins, [ 58 ] and metabolites [ 39 ] have a promising prospect. And, with the development of new omics technology and multiple immunoassay techniques, more valuable biomarker panels may be discovered in the near future.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…For such a complex disease, a biomarker panel that combines several different markers will most likely be more accurate than any single biomarker in the diagnosis of endometriosis. [ 45 ] Studies have confirmed that some biomarker panels such as peptide peaks, [ 57 ] proteins, [ 58 ] and metabolites [ 39 ] have a promising prospect. And, with the development of new omics technology and multiple immunoassay techniques, more valuable biomarker panels may be discovered in the near future.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Although the false discovery rate (FDR) can detect differentially expressed peptides more accurately than p value, we would get very few peptides by FDR. Because we found that some studies also applied the P value to the analysis of peptides [94][95][96], we also used the p value in the study. Secondly, we preliminarily explored the functions of differentially expressed peptides on H 2 O 2 -treated A549 cells, and the cellular mechanisms and target molecules of these peptides are unknown, which need more detailed studies in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Although the false discovery rate (FDR) can detect differentially expressed peptides more accurately than p value, we would get very few peptides by FDR. Additionally, in order to identify more differentially expressed peptides, some studies also applied the p value to the analysis of peptides [ 53 , 54 ]. Thus, in some condition, it is also appropriate to use the p value.…”
Section: Discussionmentioning
confidence: 99%